Peningkatan Kapasitas Manajemen Keuangan UMKMThasya Ethnic melalui Pelatihan Pencatatan Akuntansi Praktis - Arif Makhsun; M.Muhayin A Sidik; Enggar Dwi Cahyo; Yunika Marita Sari; Yola Febriani; Moch. Hidayat Nur Awaludin (Penerbit Goodwood, 2026)
Purpose: This community service aims to improve the financial management capacity of Thasya Ethnic MSMEs through practical accounting recording training to strengthen their financial literacy and reporting ability. Methodology The activity applied a participatory community engagement approach involving 15 participants from Thasya Ethnic MSMEs. Data were collected through pre-test, post-test, observation, and interviews. The training used Microsoft Excel-based accounting worksheets covering journal entries, ledgers, trial balance, income statement, and balance sheet preparation. Results: The training increased participants’ understanding and ability to record transactions, prepare simple financial reports, and separate personal from business finances. Quantitatively, financial management capacity improved by 38% after the training. Participants successfully produced structured and digitalized accounting records for September 2025. Conclutions: This practical accounting recording training proved effective in enhancing the financial management capacity of Thasya Ethnic MSMEs. The participants were able to understand the basic concepts of accounting records, prepare simple financial statements, and begin implementing routine bookkeeping in their business activities. Limitations: the study was limited to one MSME and a short training period, so long-term behavioral impact needs further evaluation. Contribution: This study contributes to the development of accounting literacy and financial management practices for creative MSMEs, supporting entrepreneurship and community empowerment education.